2008
DOI: 10.1021/jp710270z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Structure and Dynamics of the Diaquotriamminezinc(II) Complex by QM/MM MD Simulation

Abstract: The structural and dynamical properties of the cis-(O-Zn-O angle approximately 90 degrees) and trans-(O-Zn-O angle approximately 180 degrees) isomers of the model diaquotriamminezinc(II) complex in aqueous solution have been evaluated using the hybrid quantum mechanical/molecular mechanical molecular dynamics simulation approach at ab initio Hartree-Fock level. In both complexes, the first hydration shell contains five ligands (two water and three ammonia molecules) arranged in a trigonal bipyramidal geometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 50 publications
5
34
2
Order By: Relevance
“…2͒, predict 14 water molecules in the second shell region ͑3.5-4.7 Å͒ and nearly within the large range of values obtained from the analysis of the x-ray data, 45-50 7.6-13.2 waters. This number also agrees well with the results from several prior MD and QM/MM simulations 40,44,[51][52][53][54][55] and within the range of values of the conventional MD simulations. However, compared to these prior simulations our second shell maximum is found to be 5%-10% smaller.…”
Section: A the Hydration Shell Structuresupporting
confidence: 90%
See 4 more Smart Citations
“…2͒, predict 14 water molecules in the second shell region ͑3.5-4.7 Å͒ and nearly within the large range of values obtained from the analysis of the x-ray data, 45-50 7.6-13.2 waters. This number also agrees well with the results from several prior MD and QM/MM simulations 40,44,[51][52][53][54][55] and within the range of values of the conventional MD simulations. However, compared to these prior simulations our second shell maximum is found to be 5%-10% smaller.…”
Section: A the Hydration Shell Structuresupporting
confidence: 90%
“…Both the full AIMD ͑64 waters͒ and the AIMD/MM ͑one hydration shell͒ simulations give very similar results for the structural parameters and both agree fairly well with available experimental data. We note here that the QM/MM simulations ͑QM region Gaussian basis set Hartree-Fock͒ by Fatmi et al 40 observed significant structural changes in the solvent when extending their QM region to incorporate the second hydration shell of Zn 2+ that are not observed in our results. The extension of the QM region was not found to be necessary in our simulation where we found substantial agreement between the full AIMD and the AIMD/MM for the structure and dynamics with only the inclusion of the first shell.…”
Section: A the Hydration Shell Structurecontrasting
confidence: 44%
See 3 more Smart Citations